An Empirical Analysis of Mark-ups in the Argentine Manufacturing Sector - Brambilla, María Irene (2014)
In this paper, we estimate mark-ups with plant level production data for Argentina from a structural model of cost-minimizing producers, as proposed by De Loecker and Warzynski (2012). We explore systematic differences across industries and plants. Our main findings are that mark-ups are higher in capital-intensive industries, and for plants that are more productive, larger, and more capital-intensive. Our findings are consistent with theories that predict larger mark-ups for more efficient firms and for higher quality products.